THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP ON ORGANIZATIONAL COMMITMENT IN CLASS IIB GIANYAR DETENTION CENTER - Mahendra, I Putu Bayu Rama; Rifani, Denny Nazaria (Universitas Nusa Cendana, 2025)
This study aimed to determine the perception of transformational leadership on organizational commitment and the influence between transformational leadership and organizational commitment in Gianyar Detention House. This research uses quantitative research methods with non-probability sample techniques as many as 73 employees. The data collection technique was carried out using a questionnaire distributed via Google Form. There are 42 statements that are used as indicators in this study. The data analysis technique performed is through normality test, simple linear regression test, significance test and determination test which is processed using IBM SPSS software version 27. The results showed that there is an effect of transformational leadership on organizational commitment at Gianyar Detention House. The results of the determination test obtained that the tranformational leadership has an influence of 50.3% on the organizational commitment, while the remaining 49.7% is influenced by other variables not explained in this study. Keywords: Organizational Commitment; Transformational Leadership; Detention Center